Social Media, Public Sphere and Movement Discussion of Urban Farming in Indonesia - Stepanus Bo'do; Hotman Siahaan; Rachmah Ida (Budapest International Research and Critics Institute (BIRCI-Journal): Humanities and Social Sciences, 2019)
The internet and social media expand public sphere has been much associated with public sphere and digital networks in many studies, where Habermas's public sphere theory and the theory of the Castells network society have been much debated about its relevance to the techno-social development. Both Habermas and Castells tend to see the public sphere of the Internet as a contestation space where corporate and state forces work in various ways to control and dominate it. This study emphasizes more on the creativity of citizens forming community networks through the use of the Internet and social media and conducting autonomous conversations in the public sphere. Netnographic studies of the dynamics of the discourse of public sphere in the social movement networked Indonesia Berkebun show that the Internet and social media become creative means for citizens to package global discourse locally to voice their demands. This study concludes that the concepts and theories of public sphere, network society are relevant as tools for analyzing public sphere and Internet networks and social media. The potential of the Internet network and social media as autonomous communication spaces depends on the design and purpose and the utilization of available features. Conversations that are restricted to the agenda of the 3E program help communities focus on discourse and shape the character of a rational Indonesian gardening space. This community from the beginning realized the potential of the Internet and social media to form networks and public spheres. But like gardening, public sphere requires commitment, such as caring for the garden from pest attacks, weeds, giving it fertilizer so the plants grow as expected.